1911
DOI: 10.1037/h0093057
|View full text |Cite
|
Sign up to set email alerts
|

On the functions of the cerebrum: The occipital lobes.

Abstract: SHEPHERD IVORY FRANZ the brain." The remainder of the occipital lobe is considered by Campbell to be one area, while Brodmann has been able to distinguish two separate areas, which he admits are closely related (10, p. 228). The cortex surrounding the calcarine area, FIGS, i and 2. The human cerebrum, with the areal differentiation of the occipital lobe. The dotted part is the calarine type, and the parts marked by horizontal lines and by cross hatching are the remainder of the so-called visual cortex. Adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1913
1913
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Several prominent 19th century clinicians and scientists recognized and demonstrated the importance of the frontal lobes to the control of movement (Ferrier, 1886;Fritz & Hitzig, 1870/1960, language, (Broca, 1861), and personality (Harlowe, 1868). Neurobehavioral investigations of the frontal lobes continued to blossom in the early 20th century with studies of nonhuman primates (e.g., Franz, 1907;Jacobsen, 1936), patients recovering from war injuries (e.g., Feuchtwanger, 1923;Goldstein, 1942;Kleist, 1934), and individuals who underwent lobectomies for the removal of tumors and epileptic foci (e.g., Brickner, 1934;Rylander, 1939). Toward the middle of the century, psychosurgery of the frontal lobes was introduced and studies of the effects of prefrontal leucotomy abounded (e.g., Freeman & Watts, 1950;Greenblatt, Arnold, & Soloman, 1950;Greenblatt & Solomon, 1953;Monitz, 1954).…”
Section: Adult Studiesmentioning
confidence: 99%
“…Several prominent 19th century clinicians and scientists recognized and demonstrated the importance of the frontal lobes to the control of movement (Ferrier, 1886;Fritz & Hitzig, 1870/1960, language, (Broca, 1861), and personality (Harlowe, 1868). Neurobehavioral investigations of the frontal lobes continued to blossom in the early 20th century with studies of nonhuman primates (e.g., Franz, 1907;Jacobsen, 1936), patients recovering from war injuries (e.g., Feuchtwanger, 1923;Goldstein, 1942;Kleist, 1934), and individuals who underwent lobectomies for the removal of tumors and epileptic foci (e.g., Brickner, 1934;Rylander, 1939). Toward the middle of the century, psychosurgery of the frontal lobes was introduced and studies of the effects of prefrontal leucotomy abounded (e.g., Freeman & Watts, 1950;Greenblatt, Arnold, & Soloman, 1950;Greenblatt & Solomon, 1953;Monitz, 1954).…”
Section: Adult Studiesmentioning
confidence: 99%
“…This discovery in.creased the impetus to pursue other locations of function in the brain. Franz (1907) adopted standardized testing procedures to evaluate cats and monkeys before and after surgically imposing cerebral lesions. He concluded that the frontal lobes were particularly important for the solution of puzzlebox performances, and that unilateral lesions produced much less of an effect than bilateral lesions.…”
Section: Overview Of the History And Development Of Conclusion Aboutmentioning
confidence: 99%
“…In his view, the frontal cortex was the top of the sensory and motor hierarchies and was the final stage of integration. The American psychologist Franz (1907), unlike his predecessors, used structured and objective behavioral testing methods (e.g., Thorndike boxes and basic visual discrimination problems) to study the effects of frontal lobe removal. Unfortunately, though, the behavioral tests he chose proved inadequate for capturing the types of mental processes that are impaired after frontal lesions.…”
Section: Historymentioning
confidence: 99%